Teaching Indonesian for other language speakers - Widyasari, Hesti; Dardjito, Hanandyo (Technium Social Sciences Journal, 2022)
Previous studies suggested immersing the language learners in the target language when learning a foreign language. It is, to some extent, difficult to apply because of several factors; therefore, English operates as a medium of instruction in the classroom where the learners have different cultures and different first languages. This study aimed at finding out the use of English as a medium of instruction in teaching Indonesian for foreign language speakers or Bahasa Indonesia bagi Penutur Asing (BIPA). It applied a qualitative design involving a semi-structured interview with three BIPA teachers selected using purposive sampling. The interview data were analysed interpretively. The findings revealed that English was employed when giving instruction, explaining complex concepts and grammar, defining vocabulary, checking the students’ comprehension, and keeping the classroom interaction. However, English was used limitedly because the learners needed to learn and practice the target language.